Specific therapies for severe postpartum haemorrhage in the UK. (16th November 2010) - Kayem, G; Kurinczuk, J; Alfirevic, Z; Spark, P; Brocklehurst, P; Knight, M
Abstract : Background: Postpartum haemorrhage (PPH) remains an important cause of maternal morbidity and mortality. When first line managements fail, a number of specific therapies including brace sutures, factor VII, ligation and embolisation of major pelvic vessels may be used. However, there are no systematic data at a population level to assess the clinical outcomes following their use. Methods: A national descriptive study was conducted using the UK Obstetric Surveillance System between September 2007 and March 2009. Results: 295 women were treated with one or more specific therapies for PPH during the study period. 213 women (72%) had a brace suture, 32 (11%) arterial ligation, 16 (5%) arterial balloon, 43 (15%) arterial embolisation and 58 (20%) received factor VII. Interventional radiology was potentially accessible for only 126 (43%) of cases; availability was associated with a lower use of brace sutures (OR 0.42, 95% CI 0.25 to 0.70). In women who had a brace suture as their initial treatment, 23% (95% CI 17% to 30%) of cases proceeded to hysterectomy. The figure was 44% (27% to 64%) for women managed initially with factor VIIa, 53% (29% to 76%) for arterial ligation, 11% (1% to 33%) for embolisation and 18% (2% to 52%) for arterial balloon placement. Conclusion: When first line therapies have failed, brace sutures are the most common additional treatment used in cases of severe PPH in the UK. Lack of availability restricts the use of embolisation and arterial balloon placement. Further investigation, including assessment of cost-effectiveness, is needed to inform guidelines on the use of these therapies.